2012
DOI: 10.1179/1743289811y.0000000010
|View full text |Cite
|
Sign up to set email alerts
|

Production of rubber parts by tyre recycling without using virgin materials

Abstract: A new recycling technology (namely 'direct powder moulding') is proposed to produce large rubber parts from spent tyres without any addition of virgin materials or linking agents. Rubber pads were produced by compression moulding of rubber powder mixtures which were obtained by mechanical grinding of ground tyre rubbers. In this study, the effect of different powder mixtures on the final performances of the moulded parts was evaluated. Starting from three initial size distributions of the rubber powder, other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 59 publications
1
18
0
Order By: Relevance
“…A value of 0.61 ± 0.16 MPa was found for the tensile strength, 31 ± 5% for the elongation at break and 5.2 ± 0.6 MPa for the elastic modulus. These data are comparable with data obtained in laboratory for small pads 33-34 but for the first time, they have been measured on a 1-m 2 tile. A clear trend in the tile geometry is not observed but data scattering is not negligible, being about 26% for tensile strength, 18% and 12% for elongation at break and elastic modulus, respectively.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…A value of 0.61 ± 0.16 MPa was found for the tensile strength, 31 ± 5% for the elongation at break and 5.2 ± 0.6 MPa for the elastic modulus. These data are comparable with data obtained in laboratory for small pads 33-34 but for the first time, they have been measured on a 1-m 2 tile. A clear trend in the tile geometry is not observed but data scattering is not negligible, being about 26% for tensile strength, 18% and 12% for elongation at break and elastic modulus, respectively.…”
Section: Resultssupporting
confidence: 90%
“…In fact, by changing molding temperature and pressure, molded rubber density slightly changes as well. 33 As a thumb rule, in the case of 1 m 2 tile, 10 kg of GTR are necessary for each 10 mm of tile thickness. For this reason, molding tests were made by fixing the GTR weight, from 10 to 50 kg.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some good mechanical performances of the blends must be attributed to a sort of filler-like effect due to the partial carbonization of the rubber phase. This approach for treating cross-linked rubbers was followed by several other authors (Grigoryeva et al 2005;Sonnier et al 2007;Mészáros et al 2012;Montagna and Santana 2012;Gugliemotti et al 2012;Karger-Kocsis et al 2013) with good results in terms of morphology and mechanical performance. Polyurethane foams are also cross-linked systems that are difficult to reprocess.…”
Section: With a Compatibilizing Methodsmentioning
confidence: 96%
“…Other interesting results were found by adding cellulose compound to a commingled plastic stream containing HDPE, PP, PS, and PVC (Sik Ha et al 1999); in this case a maleated rubber (SEBS-g-MA) was found to promote the compatibility between the phases and to enhance the mechanical performance, the thermal stability, and the aging properties. More in detail, adding 20 % of cellulose together with as low as 5 phr of SEBS-g-MA caused a doubling of the tensile strength that maintained approximately the same values even after 6 months aging at 100 C. One of the most appealing challenges in plastic recycling is managing complex systems such as Tetra Pak ® .…”
Section: With the Formation Of Compositesmentioning
confidence: 92%